Aspects of aperiodic order - Baake, Michael; Cortez, Maria Isabel; Damanik, David; Strungaru, Nicolae (My University, 2023)
The theory of aperiodic order expanded and developed significantly since the discovery of quasicrystals, and continues to bring many mathematical disciplines together. The focus of this workshop was on harmonic analysis and spectral theory, dynamical systems and group actions, Schrödinger operators, and their roles in aperiodic order – with links into a full range of problems from number theory to operator theory.
Keywords: aperiodic order